Horizontal and Vertical Relationships in Developing Economies: Implications for SMEs' Access to Global Markets - Mesquita, Luiz F.; Lazzarini, Sergio G. (Academy of Management Journal, 2008)
We integrate the resource-based view, transaction cost economics, and institutional theory to model how collaboration among small-to-medium-sized enterprises (SMEs) in environments of weak infrastructure and institutions help them achieve greater collective efficiencies and access to global markets. Using survey data from 232 Argentine furniture SMEs, we found that different types of ties matter in different ways for these SMEs' collective efficiencies. For instance, vertical ties yield manufacturing productivity along the supply chain, while horizontal ties enable collective resource use as well as joint product innovation. These collective efficiencies, in turn, serve as competitive currencies helping SMEs access global markets.